2020
DOI: 10.1002/saj2.20040
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple, molecular dynamics‐based method to estimate the thickness of electrical double layers

Abstract: Electrical double layers (EDL) exist for all interfaces and determination of EDL thicknesses remains a difficult task. In this study, molecular dynamics (MD) simulations are employed aiming to develop a simple method for effective evaluation of EDL thicknesses. The EDL thicknesses at clay minerals/water interfaces are calculated by MD simulations and empirical Debye lengths, considering different electrolyte solutions (NaCl, KCl, CsCl, PbCl2 and CaCl2), electrolyte concentrations (0∼1.28 mol/L) and charge loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, applying a precise boundary at the interface can reduce the deviation between the EDL thickness values obtained using MD simulations and the continuum approach at a high ionic concentration. Gu et al reported that the EDL thickness differs with the ion concentration, and at a higher ionic concentration, the deviation between MD simulation and empirical Debye length is larger than that at a low ionic concentration …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, applying a precise boundary at the interface can reduce the deviation between the EDL thickness values obtained using MD simulations and the continuum approach at a high ionic concentration. Gu et al reported that the EDL thickness differs with the ion concentration, and at a higher ionic concentration, the deviation between MD simulation and empirical Debye length is larger than that at a low ionic concentration …”
Section: Resultsmentioning
confidence: 99%
“…Gu et al reported that the EDL thickness differs with the ion concentration, and at a higher ionic concentration, the deviation between MD simulation and empirical Debye length is larger than that at a low ionic concentration. 73 Effects of Dissimilar Atomistic Boundary and Hydrodynamic Property on Electroosmotic Flow. Figure 8 shows the effect of the dissimilar molecular boundary on the EOF velocity profiles obtained from both MD simulation and continuum perspectives.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Results of the mPB are qualitatively and quantitatively different from those of the original PB equation, such as a higher electrostatic potential drop across the electrical double layer (EDL) and thicker EDL for larger ions. [46][47][48][49] The counterion used in this study is Tris, whose radius estimated from atom models is approximately 4 Å, 50 larger than that of monovalent cations often used in buffer solutions. 51 Thus, the mPB equation can estimate the Δφ electrostatic potential difference between shallow and deep regions of the SNA more accurately than the original PB equation.…”
Section: Discussionmentioning
confidence: 99%
“…The most famous one, the Gouy-Chapman theory, applied the Poisson-Boltzmann equation to the diffuse double layer and obtained its analytical solution in 1910-1913 [14]. Related research works [15,16] used 1/k to calculate the thickness of the double layer and analyzed the effects of various factors, including concentration and particle shape, on it. Chang et al [17] obtained the influence of electrolyte type and surface charge density on the diffuse layer by solving the Poisson-Boltzmann equation that considers parameters such as ion radius and Minerals 2023, 13, 733 2 of 9 electrolyte concentration.…”
Section: Introductionmentioning
confidence: 99%